The Development of Online Teaching Materials for Indonesia Foreign Speaker Level 5 - Helmi Muzaki (AL-ISHLAH: Jurnal Pendidikan, 2024)
Indonesian Language Learning for Foreign Speakers (BIPA) is increasingly in demand, especially BIPA learning, which is carried out online. However, in online BIPA learning, there are still obstacles. The obstacle is the availability of BIPA online teaching materials. This research aims to produce BIPA online teaching materials that are feasible for BIPA 5 students. This study uses the ADDIE development model to Analyze, Design, Develop, Implement, and Evaluate. The resulting teaching materials are adapted to SKL BIPA 5 and consist of seven lessons that can be used for online BIPA learning. The seven units of material are natural disasters, historical places, Indonesian cuisine, short stories, let us discuss, creative poetry, and the hero. The presentation structure for each unit consists of learning objectives, pre-activity, material descriptions, practice questions, grammar notes, new vocabulary tables, and Indonesian insights. The material in each unit is designed to train the four language skills. Based on the due diligence on content, language, graphics and organization, presentation, and cultural elements in teaching materials, BIPA 5 online teaching materials are suitable for use by BIPA 5 students.